Negative Pressure Smart Patch to Sense and Heal the Wound - Xing Liu; Peng Zhao; Xiaozhuo Wu; Yawei Zhao; Feifan Zhou; Ying Luo; Xiaoli Jia; Wen Zhong; Malcolm Xing; Guozhong Lyu (Advanced Science)
Abstract Negative pressure wound therapy (NPWT) offers significant advantages in terms of rate and time for healing through generating sub‐vacuum to draw out inflammatory exudate and promote wound closure. However, continuous drainage probably leads to healing delay due to the lack of information about the real status of the wound bed and the potential risk of infection. To address this concern, printed Negative Pressure Smart Patch (NPSP) is reported by integrating smart real‐time sensing acidity (infection) and glucose, and anti‐infection into NPWT systems. In addition, NPSP delivers vancomycin through chitosan porous microspheres under negative pressure to modulate wound healing. Compared with NPWT, NPSP projects a promising approach to removing bacteria, reducing local inflammation, and accelerating healing in a short period of time.